2017
DOI: 10.1016/j.jneumeth.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of different retinal components and the effect of asymmetric pulses

Abstract: MEA recording and stimulation from the chick retina is exceptionally powerful in distinguishing between direct and indirect responses. This method facilitates comparison between different stimulation strategies. We show that asymmetric electrical stimulations allow control over the intensity of direct activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…The latency of a direct response becomes larger when detected on electrodes that are further away from the stimulating electrode. Indeed, measured propagation direction (red and blue regression lines in Figure a) and speed of 0.33 ± 0.045 m s −1 (calculated from the latency of the response between two adjacent electrodes, 500 µm apart), correspond well with fiber layer alignment (Figure c) and known action potential propagation speed in the chick retina . The photocapacitive pixels elicit the same direct response as current‐injected MEA electrodes ( n = 4 retinas), verifying that the devices are photocapacitively evoking direct retinal responses.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The latency of a direct response becomes larger when detected on electrodes that are further away from the stimulating electrode. Indeed, measured propagation direction (red and blue regression lines in Figure a) and speed of 0.33 ± 0.045 m s −1 (calculated from the latency of the response between two adjacent electrodes, 500 µm apart), correspond well with fiber layer alignment (Figure c) and known action potential propagation speed in the chick retina . The photocapacitive pixels elicit the same direct response as current‐injected MEA electrodes ( n = 4 retinas), verifying that the devices are photocapacitively evoking direct retinal responses.…”
supporting
confidence: 65%
“…In the chick retina, direct responses are easily recognized as they propagate in both directions along the nerve fibers (retrograde and anterograde). We have previously shown that these responses result from direct activation of ganglion cells, they can be suppressed by the presence of voltage‐gated sodium channels blocker, tetrodotoxin, but not in the presence of synaptic transmission blockers . The latency of a direct response becomes larger when detected on electrodes that are further away from the stimulating electrode.…”
mentioning
confidence: 99%
“…In particular, 192 trials (8 levels of pulse frequency and 24 levels of pulse amplitude at each frequency) of biphasic pulse trains were delivered to each RGC. This process is time-consuming and potentially unattainable when a large stimulation parameter space (e.g., up to the frequency of 25 kHz) is to be evaluated, or if other pulse waveform shapes are to be considered (Hadjinicolaou et al, 2015 ; Raz-Prag et al, 2017 ). In addition, responses to HFS may be variable across functionally-distinct RGC types (Cai et al, 2011 , 2013 ; Twyford et al, 2014 ) and a comprehensive description of electrically-evoked RGC responses is yet to be compiled, due to their large diversity in both intrinsic and morphological properties (O'Brien et al, 2002 ; Margolis and Detwiler, 2007 ; Wong et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unconventional waveform designs have also been explored to improve selective stimulation of specific neuronal populations inside retinal cell networks [19][20][21][22][23][24]. Sinusoidal waveforms have been suggested to preferentially activate photoreceptors, bipolar cells, or ganglion cell populations [19,20].…”
mentioning
confidence: 99%
“…Sinusoidal waveforms have been suggested to preferentially activate photoreceptors, bipolar cells, or ganglion cell populations [19,20]. Furthermore, asymmetric biphasic waveforms have been found to provide control over direct versus indirect activation of retinal cells [21]. Other studies have suggested that the duration of stimulation can be utilised to selectively activate between retinal ganglion cells, bipolar cells, and amacrine cells [22], modulate the selectivity for ON versus OFF responses [23] and produce precise temporal patterns of ganglion cell firing [24].…”
mentioning
confidence: 99%